Spiral - Suzuki, Koji; Mizuki, Sakura; Kokubo, Naomi; Hoffman, Steven; Lacuna, Wilbert (Milwaukie, OR : Dark Horse Manga, 1999)
Horror manga adaptation of Koji Suzuki$1 (Bs novel, continuing the story of cursed videotapes and supernatural events.s
English translation of the Japanese manga.
Keywords: Horror fiction; Manga; Japanese literature $v Comic books, strips, etc